TINGKAT KECEMASAN DAN TINGKAT PENGETAHUAN REMAJA PUTRI TENTANG DISMONOREA DI YAYASAN PARULIAN 4 PORSEA KABUPATEN TOBA SAMOSIR TAHUN 2018 - Manurung, Melva (Universitas Prima Indonesia, 2019)
Menstruation is the discharge of blood from the uterus caused by the release of the endometrium, the output consists of endometrial and stirmal cells. The old blood cells and other gland secretions averaged about 5 days. At the beginning of menstrual levels of extrogen and progesterone, LH decreases or is in the lowest levels during the cycle and the levels of FSH (Foullicle stimulating hoemone) just begin to increase. Sometimes menstruation with pain is termed dismonorrhea. Dismonorrhea is a painful menstrual period, dismonorrhea is usually isolated or is part of menstrual syndrome that is related during menstruation caused by uterine muscle spasms and cause pain at the time of menstruation. This study was conducted to identify the level of anxiety and the level of knowledge of young teenagers about dismonorrhoea in the Yayasan Parulian 4 Porsea of Toba Samosir Regency. By using descriptive design, 46 samples were collected using cluster sampling, data collection was conducted on May-June 2018. After analyzing the data, it is found that the respondents have good knowledge (n = 41: 89,1%) from the good knowledge expected to be the basis for the application of nursing care and improvement and health degree. Anxiety assessment categories are mild, moderate, and severe anxiety. After the research, it was found that the respondents had mild anxiety (n = 42: 91.3%). With mild anxiety is expected to reduce anxiety, worry in the face of dismonorrhoea.